Association between blooming time and climatic adaptation in Prunus mume - Shi, Ting (John Wiley and Sons Inc., 2019)

(untitled) (Ecol Evol)
Prunus mume Sieb. et Zucc. is an important fruit crop of the subtropical region, originating in China. It blooms earlier than other deciduous fruit trees, but different regions have different blooming periods. The time of anthesis is related to the dormancy period, and a certain amount of chilling promotes bud break and blooming. To identify the relationship between blooming time and the climatic adaptation of P. mume cultivars in China, the nuclear and chloroplast genomes of 19 cultivars from the main cultivation areas of P. mume in China were resequenced. The average depth of coverage was 34X–76X, and a total of 388,134 single nucleotide polymorphisms were located within the coding regions of the gene (CDs). Additionally, the 19 cultivar accessions were divided into three groups based on their blooming time: early, mid, and late. Associated with the blooming time groups, 21 selective sweep regions were identified, which could provide evidence supporting the possible model of P. mume domestication originating due to natural selection. Furthermore, we identified a flowering gene, FRIGIDA‐LIKE 3 (FRL3), seems to affect the blooming time and the climatic adaptation of P. mume cultivars. This study is a major step toward understanding the climatic adaptation of P. mume cultivars in China.